Accroissements diametriques de quelques essences en foret dense Africaine - Durrieu de Madron, L.; Nasi, Robert; Detienne, P. (2000)
This paper summarises the results of a study on the growth of 17 timber species that are commonly logged in African rainforest areas: aningre (Aningeria altissima), obeche (Triplochiton scleroxylon), bosse clair (Guarea cedrata), dabema (Piptadeniastrum africanum), dibetou (Lovoa trichilioides), iroko (Milicia excelsa), kosipo (Entandrophragma candollei), kotibe (Nesogordonia papaverifera), limba (Terminalia superba), longhi (Gambeya boukokoensis), moabi (Baillonella toxisperma), niangon (Heritiera utilis), okoume (Aucoumea klaineana), sapelli (Entandrophragma cylindricum), sipo (Entandrophragma utile), tali (Erythrophleum ivorense) and tiama (Entandrophragma angolense). The data are compared with the results of growth ring analyses carried out in Cameroon, the Central African Republic and Gabon. The data were collected in a series of sampling trips to measure trunk girths in tree plots (Cote d'Ivoire, Cameroon, Central African Republic, Ghana and Gabon). They will provide a basis for calculating rotations between potential successive logging operations within the framework of forest development projects.